Augmentation and impulsive behaviors in restless legs syndrome: Coexistence or association?. (5th July 2016) - Heim, Beatrice; Djamshidian, Atbin; Heidbreder, Anna; Stefani, Ambra; Zamarian, Laura; Pertl, Marie-Theres; Brandauer, Elisabeth; Delazer, Margarete; Seppi, Klaus; Poewe, Werner; Högl, Birgit
Abstract : Objectives: To assess the frequency of impulse control disorders (ICDs) in patients with restless legs syndrome (RLS) with and without augmentation under dopaminergic therapy in a case-control study. Augmentation and ICDs are both serious complications of dopaminergic treatment of RLS but little is known about possible associations between these drug-induced disorders. Methods: In total, 58 patients with idiopathic RLS diagnosed according to the International Restless Legs Syndrome Study Group criteria were recruited. Of these, 35 patients had augmentation. The frequency of ICD symptoms was assessed using semi-structural interviews. Results: Demographic variables did not differ between patients with RLS with and without augmentation but those with augmentation took higher dopaminergic medication than patients without augmentation. Twenty-three patients with RLS (39.7%) had ICD symptoms, with 12 patients (20.7%) having definitive ICDs. Patients with augmentation had an increased risk of expressing ICD symptoms ( p = 0.007, odds ratio 5.64, 95% confidence interval 1.59–20.02). Conclusions: Patients with RLS with augmentation have an almost 6-fold increased risk of exhibiting ICD symptoms. This implies that augmentation and ICDs are related and may share a common pathophysiology. Moreover, our results have clinical implications, suggesting that patients with RLS with augmentation should be screened for ICD symptoms.